Design of E-Procurement System In CV. W3 INDONESIA - Prasetya, Kusno; Hery, Hery; Widjaja, Andree E; Suryasari, Suryasari (Jurnal Pekommas, 2020)
This research is a part of the implementation of e-procurement in CV. W3 Indonesia. The procurement was done conventionally using paper forms which were filled and submitted to the supervisor to get approval. After that, the purchasing department would purchase the items ordered. The design and implementation of this e-procurement resulted a system that is able to improve efficiency procurement processes time, and reduce operational costs by eliminating paper that was originally used as a medium for communication and verification.